Will Judicial Activism Redefine Justice in Employment Termination Disputes Through Evidence Standards? - Abdul Karim Subhanul Akbar; Risky Agung Firnanda; Lucas Feng (Universitas Negeri Semarang, 2025)
Evidentiary challenges in employment termination disputes in Indonesia highlight a significant structural imbalance between employers and employees, primarily due to unequal access to evidence and the employer's dominance over information. This imbalance undermines the principle of equality of arms and obstructs substantive justice in industrial court proceedings. This study seeks to propose a reconstruction of the theory of legal proof through the adoption of the “Shifting of Burden of Proof + Active Judge” model as a normative and doctrinal response to these evidentiary inequalities. A doctrinal-empirical methodology is employed, combining comparative legal analysis of the European Union, the Netherlands, and Germany, where burden-shifting mechanisms are embedded within labor law frameworks. Data is collected through a review of legal literature, statutory analysis, judicial decisions, and peer-reviewed publications. Qualitative and deductive analysis is used to assess the compatibility of Indonesia’s evidentiary system with the principles of due process and substantive justice. The findings demonstrate that shifting the burden of proof can promote judicial fairness and enhance employee protection without violating procedural neutrality, provided that an active judicial role is employed to manage evidentiary asymmetries and compel disclosure of employer-held documents. The “active judge” principle, thus, acts as a corrective mechanism to restore procedural balance and ensure access to justice. This study concludes that adopting the “Shifting + Active Judge” model in Indonesia’s labor law would foster procedural fairness and substantive justice. It recommends (1) establishing judicial guidelines on the active judge principle and (2) incorporating burden-shifting rules into procedural regulations or Supreme Court decrees.